Spatial distributions of XCO2 seasonal cycle amplitude and phase over northern high-latitude regions - N. Jacobs (Copernicus Publications, 2021)
Satellite-based observations of atmospheric carbon dioxide (CO2) provide measurements in remote regions, such as the biologically sensitive but undersampled northern high latitudes, and are progressing toward true global data coverage. Recent improvements in satellite retrievals of total column-averaged dry air mole fractions of CO2 (XCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="ffa38be111dbfeee63825a71ce00a601"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-16661-2021-ie00004.svg" width="25pt" height="14pt" src="acp-21-16661-2021-ie00004.png"/></svg:svg>) from the NASA Orbiting Carbon Observatory 2 (OCO-2) have allowed for unprecedented data coverage of northern high-latitude regions, while maintaining acceptable accuracy and consistency relative to ground-based observations, and finally providing sufficient data in spring and autumn for analysis of satellite-observed XCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="7776a2a308541bd291e7ef776c0343e7"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-16661-2021-ie00005.svg" width="25pt" height="14pt" src="acp-21-16661-2021-ie00005.png"/></svg:svg> seasonal cycles across a majority of terrestrial northern high-latitude regions. Here, we present an analysis of XCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="9c5f33729a91f47302cbefbbf3b84621"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-16661-2021-ie00006.svg" width="25pt" height="14pt" src="acp-21-16661-2021-ie00006.png"/></svg:svg> seasonal cycles calculated from OCO-2 data for temperate, boreal, and tundra regions, subdivided into 5∘ latitude by 20∘ longitude zones. We quantify the seasonal cycle amplitudes (SCAs) and the annual half drawdown day (HDD). OCO-2 SCAs are in good agreement with ground-based observations at five high-latitude sites, and OCO-2 SCAs show very close agreement with SCAs calculated for model estimates of XCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="c917051b77e0245088d6c20ab845fd7e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-16661-2021-ie00007.svg" width="25pt" height="14pt" src="acp-21-16661-2021-ie00007.png"/></svg:svg> from the Copernicus Atmosphere Monitoring Services (CAMS) global inversion-optimized greenhouse gas flux model v19r1 and the CarbonTracker2019 model (CT2019B). Model estimates of XCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="9aa58b6eccc12c7532ae0c920409d13c"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-16661-2021-ie00008.svg" width="25pt" height="14pt" src="acp-21-16661-2021-ie00008.png"/></svg:svg> from the GEOS-Chem CO2 simulation version 12.7.2 with underlying biospheric fluxes from CarbonTracker2019 (GC-CT2019) yield SCAs of larger magnitude and spread over a larger range than those from CAMS, CT2019B, or OCO-2; however, GC-CT2019 SCAs still exhibit a very similar spatial distribution across northern high-latitude regions to that from CAMS, CT2019B, and OCO-2. Zones in the Asian boreal forest were found to have exceptionally large SCA and early HDD, and both OCO-2 data and model estimates yield a distinct longitudinal gradient of increasing SCA from west to east across the Eurasian continent. In northern high-latitude regions, spanning latitudes from 47 to 72∘ N, longitudinal gradients in both SCA and HDD are at least as pronounced as latitudinal gradients, suggesting a role for global atmospheric transport patterns in defining spatial distributions of XCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="52fca73a5c414b78d5528ffe5e158e66"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-16661-2021-ie00009.svg" width="25pt" height="14pt" src="acp-21-16661-2021-ie00009.png"/></svg:svg> seasonality across these regions. GEOS-Chem surface contact tracers show that the largest XCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="3f90b0203edb30533269dc42aa7d6039"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-16661-2021-ie00010.svg" width="25pt" height="14pt" src="acp-21-16661-2021-ie00010.png"/></svg:svg> SCAs occur in areas with the greatest contact with land surfaces, integrated over 15–30 d. The correlation of XCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="b9c8220be57a66a58e2bc2aa836ab32b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-16661-2021-ie00011.svg" width="25pt" height="14pt" src="acp-21-16661-2021-ie00011.png"/></svg:svg> SCA with these land surface contact tracers is stronger than the correlation of XCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="066fa01c4616a3a8c948d84d4d692083"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-16661-2021-ie00012.svg" width="25pt" height="14pt" src="acp-21-16661-2021-ie00012.png"/></svg:svg> SCA with the SCA of CO2 fluxes or the total annual CO2 flux within each 5∘ latitude by 20∘ longitude zone. This indicates that accumulation of terrestrial CO2 flux during atmospheric transport is a major driver of regional variations in XCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="7b569c2c35d4f9c105038ecc28414dc1"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-16661-2021-ie00013.svg" width="25pt" height="14pt" src="acp-21-16661-2021-ie00013.png"/></svg:svg> SCA.